PENGARUH IKLIM KERJA, DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA BADAN KEPAGAWAIAN PENDIDIKAN DAN PELATIHAN DI KABUPATEN SUMBA BARAT - Santy Silawati Saramony; I Ketut Setia Sapta; Nengah Sudja (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
The quality of an organization is seen from how much human resources it has, because human resources play an important role from all existing resources and can affect the life of an organization, whether it will be successful or not. Every organization has an effort to improve the performance of its employees for the realization of the goals set by the organization itself. Therefore, there are many efforts made to improve employee performance which is a serious challenge because the success in achieving the goals and survival of an organization depends on the quality of the performance of human resources in it, including work climate, work discipline and competence. Likewise, the Office of the Education and Training Employee Agency in an effort to improve its performance has paid attention to these three variables. This research was conducted with the aim of knowing the effect of work climate, work discipline and compensation on employee performance. This study took a sample of 47 employees through a questionnaire at the Office of the Education and Training Personnel Agency of West Sumba Regency with multiple linear regression analysis tools, correlation and Detrmination by census sampling method or saturated sample. Based on the results of the analysis conducted, the organizational climate has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Competence has a positive and significant effect on employee performance at the West Sumba District Education and Training Personnel Agency.